Development and evaluation of a highly adaptive MRF-based absorber with a large effective frequency range. (27th August 2019) - Yang, J; Sun, S S; Ning, D; Li, Z; Deng, L; Christie, M D; Du, H; Zhang, S W; Li, W H
Abstract: This work developed an MRF-based absorber aiming at using the controllable storage modulus (stiffness) of MRF in its pre-yield region to achieve a wide natural frequency variation range. In the characterization test, its damping and stiffness properties in response to different amplitude and magnetic fields were explored. A sweep frequency test was then conducted to obtain the frequency shift property of the MRF absorber and the testing results demonstrate that its relative change rate of natural frequency is high up to 1986%. A mathematical model was built to predict the resonance shifting performance of the MRF absorber under different currents. Then an evaluation system with a primary mass was built to evaluate the absorber's capability on reducing vibrations. The experimental results under single-frequency excitation show that the MRF absorber has high efficiency in reducing the acceleration of the primary system under the STFT based control. The absorption experiment under the sweeping frequency excitations was also conducted and the results indicate that the absorption point of the absorber can shift its positions as the applied current changes, and that the primary acceleration remains the minimum under the STFT based control. All of the experimental results indicate that the proposed MRF absorber is competent as a vibration reduction device.